LIQUID IMMISCIBILITY IN THE JOIN NAALSIO4-NAALSI3O8-CACO3 AT 1 GPA: IMPLICATIONS FOR CRUSTAL CARBONATITES - Lee W.J.; Wyllie P.J. (My University, 1997)
The synthetic system Na2O–CaO–Al2O3 –SiO2 –CO2 has been widely used as a model to show possible relationships among alkalic silicate magmas, calciocarbonatites, and natrocarbonatites. The determined immiscibility between silicate- and carbonate-rich liquids has been strongly advocated to explain the formation of natural carbonatite magmas. Phase fields intersected at 1.0 GPa by the composition joins NaAlSiO3O8 –CaCO3 (Ab–CC, published) and NaAlSiO4 (Ne)90 Ab10 –CC (new), along with measured immiscible liquid compositions, provide pseudoternary phase relationships for the composition triangles Ab–CC–Na 2 CO 3 (NC) and Ne90 Ab10 –CC–NC. Interpolation between these, and extrapolation within the CO2 -saturated tetrahedron Al2O3–SiO2–CaO–Na2O, provides pseudoquaternary phase relationships defining the volume for the miscibility gap and the surface for the silicate–carbonate liquidus field boundary. The miscibility gap extends between 10 and 70 wt % CaCO3 on the triangle Ne–Ab–CC at 1.0 GPa; it does not extend to the Na2O-free side of the tetrahedron. The liquidus minerals in equilibrium with both silicate- and carbonate-rich consolute liquids are nepheline, plagioclase, melitite, and wollastonite; with increasing Si/Al the liquidus for calcite reaches the miscibility gap. We use these phase relationships to: (1) illustrate possible paths of crystallization of initial CO2 -bearing silicate haplomagmas, (2) place limits on the compositions of immiscible carbonatite magmas which can be derived from silicate parent magmas, and (3) illustrate paths of crystallization of carbonatite magmas. Cooling silicate–CO 2 liquids may reach the miscibility gap, or the silicate–calcite liquidus field boundary, or terminate at a eutectic precipitating silicates and giving off CO2 . Silicate–CO2 liquids can exsolve liquids ranging from CaCO3 –rich to alkalic carbonate compositions. There is no basis in phase relationships for the occurrence of calciocarbonatite magmas with ~99 wt % CaCO3 ; carbonate liquids derived by immiscibility from a silicate–CO 2 parent (at crustal pressures) contain a maximum of 80 wt % CaCO3 . There are two relevant paths for a silicate liquid which exsolves carbonate-rich liquid (along with silicate mineral precipitates): (1) the assemblage is joined by calcite, or (2) the assemblage persists without carbonate precipitation until all silicate liquid is used up. The phase diagrams indicate that high-temperature immiscible carbonate-rich liquids must be physically separated from parent silicate liquid before they can precipitate carbonate-rich mineral assemblages. Path (1) then corresponds to the silicate–calcite liquidus field boundary, and a stage is reached where the carbonate–rich liquids will precipitate large amounts of calcite and fractionate toward alkali carbonates (not necessarily matching natrocarbonatite compositions). In path (2) the high-temperature immiscible carbonate liquid precipitates only silicates through a temperature interval until it reaches the silicate–carbonate liquidus field boundary, where it may precipitate calcite or nyerereite or gregoryite. Sövites are readily explained as cumulates, with residual alkali-rich melts causing fenitization. We can see no way in phase diagrams for vapor loss to remove alkalis and change immiscible natrocarbonatite liquids to CaCO3 –rich liquids; adjustments to vapor loss would be made not by change in liquid composition but by precipitation of calcite and silicate minerals. The processes illustrated in this model system are applicable to a wide range of magmatic conditions, and they complement and facilitate interpretation of phase relationships in the single paths represented by each whole- rock phase euilibrium study.